Codex-dp: co-design of communicating systems using dynamic programming - Jui-Ming Chang; Pedram, M. (IEEE transactions on computer-aided design of integrated circuits and systems, 2000)
We present a novel algorithm based on dynamic programming with binning to find, subject to a given deadline, the minimum-cost coarse-grain hardware/software partitioning and mapping of communicating processes in a generalized task graph. The task graph includes computational processes which communicate with each other by means of blocking/nonblocking communication mechanisms at times including, but also other than, the beginning or end of their lifetime. The proposed algorithm has been implemented and experimental results are reported.